Images of the child in preschool music education: Case studies in Australia and China. (1st December 2019) - Tao, Xiangyi; Ewing, Robyn
This article explores images of young children in preschool music curricula in an Australian and a Chinese preschool. The 'images of the child' relevant to each country are presented by including children's voices, teachers' perceptions of children's personalities and their ways of learning, and children's roles in learning as designated in official documents on early childhood education. Framed by a sociocultural perspective, this qualitative case study responds to the changing contexts of early childhood music education (ECME) in both countries. Crystallization as a methodological lens is applied to shed light on the variations and complexities from the teachers' and the children's perspectives. Data-gathering methods include document analysis, classroom observations, teachers' interviews and conversations with children. This article particularly reflects the images and experiences of the children through their own lenses and enriches the scope of current ECME research.The main findings suggest the existence of both alignment and gaps, in varying degrees, between the official policy documents, the teachers' perceptions, and the children's understandings of their musical experiences. First, images of the child in the policy articles are interpreted differently in Australia and China, and there is a marked difference between the countries in their definitions of child-centred learning in specific contexts. Finally, implications and directions for future research are suggested to facilitate children's musical exploration in preschools.